Catalytic Synthesis of PEGylated EGCG Conjugates that Disaggregate Alzheimer’s Tau - El Khoury, Anton; Seidler, Paul M.; Eisenberg, David S.; Harran, Patrick G. (Synthesis, 2021)
The naturally occurring flavonoid (–)-epigallocatechin gallate (EGCG) is a potent disaggregant of tau fibrils. Guided by the recent cryo-electron microscopy (cryoEM) structure of EGCG bound to fibrils of tau derived from an Alzheimer’s brain donor, methods to site-specifically modify the EGCG D-ring with aminoPEGylated linkers are reported. The resultant molecules inhibit tau fibril seeding by Alzheimer’s brain extracts. Formulations of aminoPEGylated EGCG conjugated to the (quasi)-brain-penetrant nanoparticle Ferumoxytol inhibit seeding by AD-tau with linker length affecting activity. The protecting group-free catalytic cycloaddition of amino azides to mono-propargylated EGCG described here provides a blueprint for access to stable nanoparticulate forms of EGCG potentially useful as therapeutics to eliminate Alzheimer’s-related tau tangles.
Keywords: (–)-epigallocatechin gallate; Alzheimer’s disease; tau disaggregation; nanoparticle conjugation; click reaction; TBTA